PERANCANGAN INFORMATION RETRIEVAL SYSTEM UNTUK DOKUMEN BERBAHASA INDONESIA DENGAN MENGGUNAKAN EXTENDED BOOLEAN - Steven Steven (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Information retrieval system is a system that is designed to find documents that satisfies user’s information needs. User represents his information needs in words. The word will represent the same word in documents and it’s called query. System will retrieve all relevant documents and show it to the user. This paper will describe an information retrieval system using extended boolean method. There are two methods in this system, boolean method for retrieval process and vector space method for ranking process.